Sijasynkretismi morfologian koetinkivenä - Grünthal, Riho (Tartu University Press, 2011)
Syncretism and the overlapping of morphologi- cally distinct units or entire categories have different influences on morphosyntactically cumulative and less cumulative forms. The Finnic languages, in comparison to the more eastern Finno-Ugric languages, mainly display morphologically less complex forms. Morphologically there is a clear distinction in the way syncretism is manifested in the Finnic languages that, consequently, is one of the most distinct features in the inflectional system despite the close ge- nealogical affinity. This can concretely be seen in the differences in the case inflection of the southern, such as Livonian, Estonian and Votic, and northern Finnic languages, most notably Finnish, Karelian and Veps. The comparison of syncretism in these languages shows both cross-linguistic regularity and language-specific rules that determine syncretic forms. Diachronic change and the erosion of suffixal ele- ments are closely involved in the rise of syncretism. The paper exam- ines the symmetries and asymmetries in the occurrence of syncretic forms in Finnic case paradigms. Peer reviewed